Reflection of Phonetic Peculiarities of Dialect Speech of Old Residents of Far North-East of Russia in Historical and Ethnographic Texts - O. E. Shepileva (Научный диалог)
The article is devoted to identifying the possibilities of using historical and ethnographic sources for the study of living dialect speech. The relevance of the study is due to the need to study dialect material, part of which today is a fact of the history of the language. The novelty of the research is seen in the fact that each written language fact introduced into scientific circulation is valuable, because it allows to characterize the Siberian starozhilchesky speech or to reconstruct dialect phenomena of the past. The paper provides an overview of the main directions related to the study of Russian starozhilchesky speech in the Far North-East of Russia. The author raises the question of the value of the texts of local business writing, allowing to restore the phonetic features of the folk speech of the past. Special attention is paid to both general and specific notes of observers who recorded the originality of the Russian starozhilchesky speech. Some phonetic phenomena of dialect nature, which received repeated fixation in the considered sources, are considered. On the example of separate language fragments the author proves the reliability and content of linguistic material presented in the historical and ethnographic literature about the Far North-East of Russia. The paper gives examples illustrating local phenomena in the starozhilchesky speech, substantiates the value of written sources for the study of living dialect material.